2008
DOI: 10.1210/en.2007-1521
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Cytokine-Induced Neutrophil Chemoattractant in Hypothalamic Thermoregulation of Luteinizing Hormone-Releasing Hormone

Abstract: We demonstrated in a previous study that serum IL-8 concentrations were significantly higher in women with hot flashes than without hot flashes. To clarify the role of IL-8 in the pathoetiology of menopausal hot flashes, we examined the effect of rat cytokine-induced neutrophil chemoattractant (CINC), a member of the IL-8 family, on thermoregulation using ovariectomized (OVX) rats treated with intracerebroventricular (i.c.v.) injection of LHRH agonist (LHRHa) as a model of hot flashes. We found that: 1) expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…In addition, we showed that oral ET increased IL-8 level, but that transdermal ET decreased IL-8 level. In our previous study, we found that elevated level of cytokine-induced neutrophil chemoattractant, a member of the IL-8 family, was reduced by E 2 and that elevated skin temperature in ovariectomized rats was reduced by treatment with injection of a luteinizing hormone-releasing hormone agonist (22). This result observed in rats was also observed in women with hot flashes in the transdermal group in the present study.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, we showed that oral ET increased IL-8 level, but that transdermal ET decreased IL-8 level. In our previous study, we found that elevated level of cytokine-induced neutrophil chemoattractant, a member of the IL-8 family, was reduced by E 2 and that elevated skin temperature in ovariectomized rats was reduced by treatment with injection of a luteinizing hormone-releasing hormone agonist (22). This result observed in rats was also observed in women with hot flashes in the transdermal group in the present study.…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, although both the decreased level of plasma acylated ghrelin and the elevated level of gastric body acylated ghrelin were restored to basal levels 4 h after icv injection of UCN, the levels of des-acylated ghrelin were not restored. Ghrelin-producing cells exist as two types in the rat gastrointestinal tract (26), closed-and opened-type cells. Acylated ghrelin exists in closed-type cells, while des-acylated ghrelin exists in both closed-and opened-type cells (25).…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative gene expression analysis was performed by real-time RT-PCR according to a procedure described previously (26). TaqMan Gene Expression Master Mix (Applied Biosystems) and Assays-on-Demand Gene Expression probes (GHRL: Rn00572319_m1; FOS: Rn02396759_m1; S18rRNA: Hs99999901_s1; RPS29: Rn00820645_g1; Applied Biosystems) were used in subsequent PCR reactions according the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently it has been demonstrated than serum IL-8 concentrations were signifi cantly higher in women with hot fl ashes than those without. IL-8 could play an important role in the pathoaetiology of hot fl ashes [34,35].…”
Section: Hypothalamic Hypothesismentioning
confidence: 99%